The influence of rolling bearing parameters on the nonlinear dynamic response and cutting stability of high-speed spindle systems. (February 2020) - Xu, Kunpeng; Wang, Bo; Zhao, Zixu; Zhao, Feng; Kong, Xiangxi; Wen, Bangchun
Highlights: A method considering nonlinear factor in high-speed spindle system is proposed, which include the law of bearing joint dynamic characteristics changing with speed. The modeling method of spindle-holder joint and the holder-tool joint is studied. The effect of centrifugal force and gyroscopic moment is considered during high-speed spindle system analyzing. Abstract: In modern industry, thinner, lighter, curved and complex-surface work-pieces are playing a more and more important role in mechanical assemblies. Therefore, the quality and the machining precision requirements of the work-pieces are also getting higher and higher. In order to get higher machining accuracy and stability, the simplified nonlinear factors should be considered. In this paper, a five-degrees-of-freedom (five-DOF) model of angular contact ball bearings and a complete high-speed dynamic model with the combination of spindle-holder-tool joints are established. The laws of bearing characteristic parameters changing with pre-load and bearing speed are analyzed including contact angle, normal contact force and axial deformation. Finally, the nonlinear characteristic influences of high speed on angular contact ball bearings are introduced into the whole spindle system in the form of bearing parameters, furthermore, the nonlinear dynamic responses and stability influences of high-speed spindle system at bearing and tool point are studied. The results provide a theoretical basis and an evaluating criterion for nonlinear stability prediction and product surface quality improvement.